Stable Solid Dispersion Incorporated Sustained Release Oral Gel of 23 mg Donepezil Hcl: Pharmaceutical Science-Pharmaceutics for effective drug dosage - R. Anudeep Reddy; Dr.P.K. Lakshmi (International Journal of Life Science and Pharma Research, 2022)
The objective of the present study is to formulate and evaluate stable solid dispersion incorporated sustained release oral gel of donepezil Hcl. Solid dispersions were prepared using HPMC K100M and stearic acid using physical mixture, co-grinding and fusion methods and incorporated into the previously prepared gel bases using sodium CMC and sodium alginate and suitable formulation was optimised. All the formulations were subjected to physicochemical evaluation parameters. Solid dispersions of donepezil were prepared with HPMC K100 and stearic acid by using different methods like physical mixtures, co grinding and fusion method in the ratios of 1:1, 1:2 and 1:3. From the invitro dissolution studies, it was found that SD made by co grinding and fusion method showed sustained release and were selected and incorporated into the gel formulations made of SCMC 4% and sodium alginate 4%. The release studies of solid dispersion incorporated gel SD-HPMC K100M showed (SDG1) 87.55% and (SDG2) 88.9% at 8th hour and SD-stearic acid showed (SDG3) 83.26% and (SDG4) 82.57% at 8th hour. It was concluded that stearic acid solid dispersions incorporated in sodium CMC gels (SDG3) were optimised using short term stability studies with no leakage of drug in comparison to solid dispersions of HPMC K100M in sodium CMC gel l. Physico-chemical evaluation parameters were carried out for optimised formulations and found to be within limits. The optimized SD incorporated gel formulation of donepezil can be an alternative to SR tablet in improving the compliance of the geriatric patients.